Sickle cell disease and thalassaemia antenatal screening programme in England over 10 years: a review from 2007/2008 to 2016/2017. Issue 4 (26th November 2019) - Weil, Leonora G; Charlton, Matthew RM; Coppinger, Cathy; Daniel, Yvonne; Streetly, Allison
Abstract : Objectives: To evaluate the antenatal sickle cell and thalassaemia screening programme in England over 10 years from 1 April 2007 to 31 March 2017. Methods: Four routine data sources were used: antenatal screening laboratory data; key performance indicator data from maternity trusts; prenatal diagnosis (PND) laboratory data and data from screening incidents. Results: For the 10 years examined a total of 6608 575 booking samples were reported as screened, and 154 196 pregnant women required further testing. There were 3941 reported PND tests of which there were 964 affected fetal results. Antenatal test coverage and Family Origin Questionnaire completion rates are high and increasing; the proportion of tests declined has decreased. However, there is wide variation in the timing of antenatal tests and completeness of follow-up and testing. Since 2014/2015 a lower proportion of PND tests are performed by the programme standard of 12+6 weeks. Results suggest that PND timing affects reproductive choices as those with an affected fetus identified by PND testing earlier are more likely to terminate the pregnancy. Conclusions: The screening programme appears to be widely accepted as part of routine antenatal care in England. However, the timeliness of screening and subsequent PND testing has consistently not met programme standards. Improving timeliness would enable individuals to consider their options to make informed choices for their pregnancies at the appropriate time. This paper reports carrier rates for an almost complete cohort of women which provides important epidemiological information on the genetic profile of women in England.